The meaning of faith and transformation of religious practices among muslim middle-aged career women - Siti Marziah Zakaria,; Bazilah Raihan Mat Shawal, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Middle-aged career women looking to assess the improvements brought on by life, would probably give some forethought to their aging years, like where they have gone to, and what they have been doing. They reassess their priorities and make changes to their goals and orientations to command a higher purpose in all aspects of life. Many theorists believe, an older woman’s successful navigation of work-life balance is associated with her having a strong faith. Thus, a qualitative research was conducted to explore the meaning of faith from the perspectives of middle-aged Muslim career women. It also identified the transformation of religious practices performed by these women as they reach middle life. A few rounds of semi-structured interviews were conducted with 10 middle-aged Muslim working class women from different levels of education, career, income and health. The research adopted a purposive maximum variation sampling technique in order to have a variety in the respondents’ profiles, before transcribing and analysing all interview data in Nvivo software. What followed was a thematic analysis to identify themes and sub-themes of the data. The results showed that the respondents’ perspectives on faith rested on four meanings; 1) guide and way of life, 2) principle of life, 3) obedience, and 4) source of peace. This research also identified five central themes of the transformation being investigated; 1) inculcating religious values, 2) attending religious talks, 3) reciting and understanding the Quran, 4) improving the quality of prayer, and 5) dhikr and supplication were cited as the most visible manifestations of the transformation. It is hoped that these findings will provide a clearer understanding into the spiritual and internal growth of middle-aged Muslim career women. Apart from strengthening the works on developmental psychology in Malaysia, this research can tap on contribution opportunities, ranging from benefiting counsellors and social workers in their programs planning to enhance the psychological well-being of middle-aged Muslim working class women in Malaysia.